2015
DOI: 10.2105/ajph.2014.302441
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Cross-Sectional: Neighborhood Poverty Histories and Preterm Birth

Abstract: Neighborhood poverty histories may contribute to an understanding of perinatal health and should be considered in future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 27 publications
3
35
1
Order By: Relevance
“…Our results contrast with prior work documenting worse physical health outcomes with longer exposure to high-poverty neighbourhoods 13 14. For sense of control, brief exposure to high-poverty neighbourhoods may be detrimental because new residents have not yet developed the necessary strategies to respond to issues that arise from living in a high-poverty neighbourhood 34.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results contrast with prior work documenting worse physical health outcomes with longer exposure to high-poverty neighbourhoods 13 14. For sense of control, brief exposure to high-poverty neighbourhoods may be detrimental because new residents have not yet developed the necessary strategies to respond to issues that arise from living in a high-poverty neighbourhood 34.…”
Section: Discussioncontrasting
confidence: 99%
“…5 Gaskins et al examined the role of poverty and race on diabetes prevalence and found individual poverty increased odds of having diabetes for both black and white races, while living in areas of geographic poverty increased incidence of diabetes in the black population as a whole but only in the white population who were poor. 6 Higher incidence of preterm birth in neighborhoods with high poverty levels was reported by Margerison-Zilko et al 7 This research compared neighborhoods with low and high poverty levels, suggesting that the degree of poverty influences health outcomes.…”
Section: Introductionmentioning
confidence: 74%
“…Income inequality theory emphasizes that relative deprivation and social stratification, more than direct effects of deprivation of physical living conditions, are a causal link with poor health outcomes (33). In a test of this principle, associations between longitudinal neighborhood poverty trajectories and preterm birth were compared among neighborhoods with long-term low poverty, those with long-term high poverty, and those that experienced increasing poverty early in the study period (34); the latter two neighborhood types had 41 and 37% increased odds of preterm birth (34). The finding that high (compared with low) cross-sectional neighborhood poverty was not associated with preterm birth (35) supports a relative deprivation thesis.…”
Section: Socioeconomic Stressors and Infant And Child Healthmentioning
confidence: 99%